High-recovery sorting of cancer cells from whole blood via periodic-focusing inertial microchip. Issue 20 (13th September 2022) - Li, Xiao; Yang, Yijia; Villareal, Sarah C.; Griffin, Kitiara; Pappas, Dimitri
Abstract : Inertial microfluidic devices continue to show promise for label-free separation of cells from liquid biopsies and other biological samples. Abstract : Inertial microfluidic devices continue to show promise for label-free separation of cells from liquid biopsies and other biological samples. Serpentine-channel microfluidic devices capitalizing on inertial forces such as Dean flow have been demonstrated for cell separation, but are limited in performance due to the magnitude of the inertial lift and drag force gradients across the separation channel. We have developed a new flow design that uses periodic channel contractions to enhance the magnitude of the force gradient. Separation recover was 97% with the final sorter output consisting of 78% target cells. Separation efficiency was 87% for whole blood, which could be increased to 97% if the sample was diluted prior to sorting. The enrichment of cancer cells was over 1000-fold, and sorted cancer cells maintained a viability of 93.8% for 96 hours after sorting. In the analysis of blood plasma, breast cancer cells from a clinical patient were enriched 20×. The incorporation of periodic channel contractions in a Dean flow circuit resulted in an increase in Dean flow gradient according to simulation, resulting in sorting of small-diameter cancer cells in blood samples.